AB0177 Human Umbilical Cord Mesenchymal Stem Cells Inhibit Follicular Helper T Cell Expansion in B6.Mrl-Faslpr Lupus Mice. (9th June 2015) - Zhang, Z.; Feng, X.; Deng, W.; Huang, S.; Yao, G.; Chen, W.; Sun, L.
Abstract : Background: Follicular helper T (Tfh) cells have been implicated in the pathogenesis of autoimmune diseases. Human umbilical cord mesenchymal stem cell (hUC-MSC). Transplantation could alleviate disease progression in both lupus mice and patients. However, the mechanism is largely unknown. Objectives: The objective of this study was to explore modulatory effects of hUC-MSCs on Tfh cells in B6.MRL-Fas lpr lupus mice. Methods: The percentages of spleen Tfh cells in B6.MRL-Fas lpr lupus mice and C57BL/6 (B6) mice were examined by flow cytometry. Serum IL-21 levels were measured by ELISA. The correlations between the percentage of spleen Tfh cells, serum IL-21 concentrations and lupus-related manifestations of B6.MRL-Fas lpr mice were analyzed by Pearson's correlation test respectively. CD4+ T cells were isolated from the spleen of B6.MRL-Fas lpr mice and cocultured with hUC-MSCs for 3 days at different ratios (100:1, 20:1, 4:1), and then the frequencies of CD4+CXCR5+PD-1+T cells were determined by flow cytometry. The differentiation, proliferation and apoptosis of Tfh cells were also analyzed by flow cytometry after cocultured with hUC-MSCs. 1×10 6 hUC-MSCs were injected into B6.MRL-Fas lpr lupus mice via tail vein and the control groups were administered with 1×10 6 fibroblast-like synoviocytes (FLSs) and PBS respectively. 4 weeks later, all the mice were sacrificed. The percentages of spleen Tfh cells and plasma cells were examined by flow cytometry. CD4+CXCR5+Tfh cells were isolated from spleens of all the administered mice and cocultured with B220+cells isolated from spleens of B6 mice. 5 days later, IgG level of the coculture supernatants were measured by ELISA. Results: The percentages of spleen Tfh cells and serum IL-21 concentrations in lupus mice were significantly higher than those in B6 mice. Both the frequencies of spleen Tfh cells and serum IL-21 levels were positively correlated with serum IgG, ANA and ds-DNA antibody levels in lupus mice. HUC-MSCs could suppress Tfh generation when cocultured with CD4+T cells at different ratios. The differentiation, proliferation and apoptosis of Tfh cells could all be inhibited by hUC-MSCs in vitro. 4 weeks after hUC-MSC transplantation, the percentages of spleen Tfh cells and plasma cells were significantly lower than those in control groups. Supernatants of B220+cells cocultured with CD4+CXCR5+Tfh cells isolated from spleens of hUC-MSC treated lupus mice had lower levels of IgG than control groups. Conclusions: HUC-MSCs could inhibit Tfh expansion in B6.MRL-Fas lpr lupus mice, which may be a mechanism of hUC-MSC transplantation alleviating lupus. Disclosure of Interest: None declared